Collateral ventilation - Gompelmann, Daniela; Eberhardt, Ralf; Herth, Felix (Respiration, 2013)
Although known for more than 80 years, ‘collateral ventilation' (CV) became a focus of endoscopic research in the recent decade. Implantation of one-way valves presents an effective treatment option for patients with advanced heterogeneous emphysema optimizing symptoms and quality of life. However, this treatment modality is only successful in case of low interlobar CV. Based on this evidence, attempts to develop different approaches for the quantification of CV have been initiated. In this regard, it is crucial to illuminate the meaning and different aspects of CV.
Gesehen am 18.02.2020